Investigating Factors Related to the Employment of graduates of knowledge and information science - Zahra Sadrabady; Mahdi Mohammadi (علوم و فنون مدیریت اطلاعات, 2021)
Aim: To gain a proper job position for graduates of knowledge and information science related to their studies and more graduates in this field who can experience specialized job opportunities, it is essential to investigate the factors associated with their employment. The purpose of this study is to investigate the factors related to the employment of graduates of knowledge and information science. Methodology: This study is an applied research using a descriptive survey method that is done with a researcher-made questionnaire. Its statistical population consists of all graduates in the field of knowledge and information science of Qom University, 402 people. 302 people completed the questionnaires. Findings: The findings showed that there is a significant relationship between the level of education of individuals with the rate of employment as well as occupations related to the field. "Lack of work" was the main cause of unemployment and the "inadequate labor market" was the major factor in the employment of unrelated jobs. 61/9% of the respondents said that the effect of total academic factors on graduates' employment growth, was high or very high. Some of these influential factors are the Existence and growth of the University Scientific Community, The University's relationship with other organizations and institutions with activities that are related to the field, Introducing collegians to organizations and centers with related activities by the University for Internship, honorary work and gaining experience, etc. Personal interest (35.5%) and appropriate working environment (24.2%) are the most important reasons for continuing to work in the occupations related to the field. Also, most of the respondents considered that practical courses and specialized lessons meet the needs of related jobs. The length of time of employment is also associated with a desire to change jobs. Conclusion: According to the findings, increasing the level of specialized education in this field can increase the chances of employment. In the respondents' opinions planning to implement academic factors affects their employment status, and job stability depends on resolving job problems (such as low salaries and benefits), personal interest in the job, and appropriate work environment.